1981
DOI: 10.1080/01490458109377771
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial weathering of rapakivi granite

Abstract: Rapakivi granite samples were incubated with Pseudomonas aeruginosa culture solutions in order to elucidate the possible role of bacteria in rapakivi (crumbling stone) disintegration. SEM micrographs showed micromorphological alterations on the incubated rapakivi surface at 21 to 23°C for 20 days. Elevated concentrations of Na, Ca, K, Fe, and Mg were detected in the culture solutions after incubation. Elemental oxide ratios [K 2 O : (Na 2 O + CaO)] in culture solutions were similar to those in rapakivi ovoids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…on the basis of partial 16S rRNA gene sequencing (10). Vuorinen et al (41) observed elevated concentrations of K, Ca, Fe, Na, and Mg in the culture solutions of Pseudomonas aeruginosa after incubation in the presence of Rapakivi granite. So far, no mineral weathering experiments with green algae, which are often present on rock surfaces (17), were performed.…”
Section: Discussionmentioning
confidence: 99%
“…on the basis of partial 16S rRNA gene sequencing (10). Vuorinen et al (41) observed elevated concentrations of K, Ca, Fe, Na, and Mg in the culture solutions of Pseudomonas aeruginosa after incubation in the presence of Rapakivi granite. So far, no mineral weathering experiments with green algae, which are often present on rock surfaces (17), were performed.…”
Section: Discussionmentioning
confidence: 99%
“…They thus change the local pH [69], whereas chemo-organotrophic bacteria and fungi can release chelating organic compounds [70] or weaken the structure by oxidizing metal cations such as Fe 2+ or Mn 2+ [71].…”
Section: (%) T I (°C)mentioning
confidence: 99%
“…Sulfate is produced from oxidation of sulfide minerals that are accessorily present in basement rocks, mostly pyrite and pyrrhotite. The oxidation consumes oxygen dissolved in the recharge and is commonly biomediated (Vuorinen et al 1981). Acidity produced by the sulfate reactions is consumed by (Vovk 1987).…”
Section: Water In the Continental Upper Crust: Variability And Commonmentioning
confidence: 99%